Low fluctuation stiffness design method for vibration reduction of helical gears - YOU Zhiwei; GAO Jingtao; LI Haonan; SUN Zhou; XUE Cheng (Jixie chuandong)
ObjectiveThe time-varying mesh stiffness of gear pairs, as one of the most important internal excitation of the gear system, is an important reason for the vibration and noise of the gear system. In previous studies, tooth surface modification and shock absorber were often used to improve the vibration response of the system, but there are few literature on the influence of mesh stiffness fluctuation on the vibration characteristics of the system. In order to improve the vibration characteristics of the helical gear system, a design method of low fluctuation mesh stiffness was proposed.MethodsSince the length of the contact line of the helical gear pair changes during the meshing process, resulting in mesh stiffness fluctuations, the core idea of the design method was to deduce the conditions for the minimum change of the total length of the contact line in the meshing process according to the mesh principle. Then it was compared with the finite element method to verify the correctness and effectiveness of the parameter design method and the analytical mesh stiffness model. A dynamic model of eight-degree-of-freedom helical gear was established. Then the RMS of vibration energy before and after optimization was compared. The loaded static transfer error (LSTE) and dynamic response were analyzed, and two optimization design methods were discussed.ResultsThe results show that appropriate parameter design can significantly reduce the mesh stiffness fluctuation, optimize the LSTE and improve the vibration of the system. The research results provide theoretical support for the vibration reduction design of the gear system.